Plasma Cells In Endometrium In Chronic Endometritis - Nasreen Rehmatullah, Fatimah Sarwar, Fakhra Ashique, Fouzia Rahat, Qudsia Niazi, Ummehabiba, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To establish significance of presence of plasma cells in endometrium and their possible relationship with various underlying morbidities. Study Design: Retrospective Study Methods: A total of 50 diagnosed cases of chronic Endometritis, based on presence of stromal plasma cells were identified and retrospectively, they were evaluated for their main presenting complaints between 2011-2014 in KRL General Hospital, Islamabad. Prevalence and factors of chronic Endometritis were assessed. SPSS 22.0 was used to analyze all data. Results: Out of 50 patients 30 (60%) cases were associated with Abnormal vaginal bleeding, 8 (16%) with subfertility, 6 (12%) with Abortion and 6(12%) with non-specific cervicitis. Conclusion: Chronic nonspecific endometritis is not uncommon but in fact is under diagnosed condition. It is strongly associated with heavy irregular menstrual bleeding, subfertility and abortions. This important topic is still under research. Further work is needed on diagnosis and definitive treatment of this problem. Key words: Plasma cells, Endometrium, Endometritis, Abnormal vaginal bleeding, Sub-fertility